ENVIRONMENTAL EDUCATION AS AN INSTRUMENT FOR IMPROVING THE MONTHLY SANITATION EXERCISE IN KANO METROPOLIS - Kabuga, Adamu Ibrahim (PEOPLE: International Journal of Social Sciences, 2019)
The Paper discusses some observable environmental problems resulting from man’s continuous interaction with the environment in kano metropolis. It was found necessary to use environmental education as an instrument to educate the people for better improvement of the monthly environmental sanitation exercise in the state. The monthly environmental sanitation exercise is carried out in the state at the end of every month in the last Saturday of the month. The exercise usually last for 3 hours starting from 7:00a.m to 10:00am with the hope of cleaning and keeping the environment tidy. Field observation and questionnaire were used to generate data for the study. The simple random sampling technique was used to select samples needed for the study. Tables and percentages were used to analyze the date. The study found that many people in the city usually seat at their homes within the said hours without cleaning or doing anything during the exercise. It was also found that the exercise is not properly monitored or supervised in the metropolis, except in some major roads and high ways leading to the city. The study recommends that environmental education is an important instrument that can be used to improve the monthly sanitation exercise in the metropolis. Social media and GSM text messages can equally be used to disseminate information to the general public on the exercise for effective participation in the city. Civildefense, Kano Road Traffic Agency (karota) and Kano state Hisbah Board (Hisba) personals should be involved in the exercise for more proper participation and effectiveness.